Influence of lockdown during the COVID-19 pandemic on use of pediatric emergency health services: A retrospective observational study from a Tertiary Care Hospital in New Delhi - Ravitanaya Sodani; Shalu Gupta; Ankita Goel Sharma (Wolters Kluwer Medknow Publications, 2023)
January 30, 2020, marked the beginning of the COVID-19 pandemic in India. Various emergency measures were taken to contain the spread of COVID-19 including extended periods of complete lockdown. The impact of these measures on routine and emergency health services was unforeseen. Hence, we conducted this study to critically analyze the effects of restrictions imposed during the COVID-19 pandemic (including lockdown) on the utilization of health services, especially emergency services. We compared patient's attendance in the outpatient department and pediatric emergency department (PED) and changes in clinicepidemiological profiles (before and during COVID-19) in a tertiary care hospital. We observed a 43% decline in PED visits which decreased to 75% during the period of strict lockdown (P = 0.005). Reduction in emergency department visits was noticed uniformly in all disease categories. This study highlights the urgent need to plan for robust health-care support system for the delivery of preventive and curative services to vulnerable age groups during any emergency.